Climate change adaptation and adaptive efficacy in the inland fisheries of the Lake Victoria basin. Issue 5 (19th August 2022) - Nyboer, Elizabeth A.; Musinguzi, Laban; Ogutu‐Ohwayo, Richard; Natugonza, Vianny; Cooke, Steven J.; Young, Nathan; Chapman, Lauren J.
Abstract: Inland fisheries support the livelihoods of millions of people in riparian communities worldwide but are influenced by increasing climate variability and change. Freshwater fishing societies are among the most vulnerable to climate change given their dependence on highly threatened aquatic resources. As climate change intensifies, building adaptive capacity within communities and understanding the efficacy of adaptive strategies for maintaining household stability is essential for coping with ongoing social and environmental change. In this study, we examined household perceptions of climate change, livelihood impacts and responses to socio‐ecological changes in fishing‐dependent households in the Lake Victoria basin in Uganda, East Africa. Through a series of household surveys and focus group discussions in five fish landing sites, we assessed social adaptive capacity (SAC) based on 207 households and identified adaptive strategies that are effective for coping with climatic change. We found that people in fishing households are aware of environmental change but that most households do not have adaptive strategies that are efficacious for securing long‐term income and food security. We also investigated household demographics that contribute to SAC, examined links between SAC and adaptive efficacy and established potential routes towards developing effective adaptive approaches in small‐scale fisheries. This work contributes to a growing foundation of documented community‐based knowledge for building adaptive capacity in inland fisheries and the communities around the world that depend on them. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.